2021
DOI: 10.1111/ajt.16500
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between QT interval prolongation and structural abnormalities in cirrhotic cardiomyopathy: A change in the current paradigm

Abstract: It is postulated that cardiac structural abnormalities observed in cirrhotic cardiomyopathy (CCM) contribute to the electrophysiologic abnormality of QT interval (QTc) prolongation. We sought to evaluate whether QTc prolongation is associated with intrinsic abnormalities in cardiac structure and function that characterize CCM. Consecutive patients undergoing liver transplant work‐up between 2010 and 2018 were included. Measures of cardiac function on stress testing including cardiac reserve and chronotropic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…However, patients with LVDD had a significant longer QTc, a trend for higher BNP and a trend to older age. QTc interval prolongation has been correlated with the severity and complications of cirrhosis in several previous studies, but data are still controversial [28,29]. In our study, a significant but not so strong correlation was found between the QTc and Child-Pugh score.…”
Section: Discussionsupporting
confidence: 47%
“…However, patients with LVDD had a significant longer QTc, a trend for higher BNP and a trend to older age. QTc interval prolongation has been correlated with the severity and complications of cirrhosis in several previous studies, but data are still controversial [28,29]. In our study, a significant but not so strong correlation was found between the QTc and Child-Pugh score.…”
Section: Discussionsupporting
confidence: 47%
“…A prolonged QT interval is the main electrophysiological signature of CCM, which is associated with 30-day cardiovascular AEs and mortality, post-LT (30,31). In the 2019 CCC consensus, QT prolongation was not warranted, because of its limited value in the diagnosis of CCM (32,33). Potassium is the major predictive factor of perioperative cardiovascular AEs.…”
Section: Discussionmentioning
confidence: 99%
“…However, what role these mechanisms play in the genesis of repolarization abnormalities in cirrhosis remains unclear. Indeed, a recent study by Koshy et al 84 demonstrated no correlation between LQTS and either the 2005 World Congress of Gastroenterology or 2020 Cirrhotic Cardiomyopathy Consortium diagnostic criteria for cirrhotic cardiomyopathy,suggesting that LQTS and cirrhotic cardiomyopathy are separate and unrelated phenomena. However, this conclusion is controversial, with some believing that he presence of cirrhotic cardiomyopathy may contribute to the manifestation of LQTS, and also increase the risk of fatal arrhythmias.…”
Section: Acquired Lqts In Cirrhosismentioning
confidence: 99%